Characteristics of Implementing Practice Development in Germany: A National Scoping Review - Anne Fahsold; Theresa Siegler; Anna Louisa Hoffmann‐Hoffrichter; Sibylle Reick; Rebecca Palm (Health Science Reports)
ABSTRACT Background and Aims Practice development is a clearly defined concept internationally. In Germany, however, the concept is understood differently. For this reason, it is unknown how the concept is implemented in patient care and whether it corresponds to the international concept. The aim was to create an overview of practice development projects in Germany and to examine whether the practice development projects included meet the internationally defined criteria for practice development. Methods A scoping review was performed. For this purpose, a literature search was conducted in MEDLINE, CINAHL, CareLit, and GeroLit as well as by hand search in nonindexed German‐language journals. Articles were included in the evidence synthesis regardless of their methodological quality. Results Eleven articles from 2012 to 2021 were included in the scoping review. The goals pursued by the projects focus on the implementation of evidence‐based nursing and advanced practice nursing, the integration of university‐trained nurses, the improvement of clinical care, and the competence development of nurses and leaders in the acute hospital setting. The review showed that few practice development projects incorporate the internationally recognized criteria of practice development and are based on the current international definition of practice development. Conclusion It would appear beneficial and necessary to achieve a uniform understanding in Germany to undertake a process of concept clarification and to develop a definition of practice development for implementation.